Issues & Challenges of Baitul Maal Wa Tamwil (BMT) In Financing the Poor During Pandemic Covid-19: A Systematic Literature Review of Evidence - Andri Martiana; Richa Angkita Mulyawisdawati; Muhammad Shivalingga Hero Pratama (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
COVID-19 is a virus that attacks Islamic non-bank financial institutions, such as Islamic microfinance institutions (IMFI). BMT's presence is useful for freeing people from the usury system and promoting justice; it is also meant to act as a link between Islamic beliefs and poverty alleviation. A systematic review aims to provide a detailed, unbiased synthesis of multiple relevant studies. Conventional literature review felt lacks a formal methodology for monitoring the impact of a therapy, a far more methodical approach is necessary. This article aims to discover Pandemic covid-19 impact to BMT by means of a systematic literature review. The advancement of BMT literature during the COVID-19 pandemic may be divided into four categories namely by year of study, kind of published document, based on the research approach, and based on the type of research. Result of the study explained that COVID-19 pandemic has an impact on BMT activities such as the fluctuating level of development in the number of Non-Performing Financing. The phenomenon of non-performing financing is also found in several BMTs. The role of BMT in the economic empowerment of the lower economic community includes the role in the development of MSMEs and its impact on business development (total assets, income, profits, and business stability) and decrease unemployment through employee recruitment. Future study can use a quantitative and/or mixed method approach. The study's object can be expanded by expanding the research object and/or do content analysis/library research/conceptual research.